2017
DOI: 10.1093/jbcr/irx010
|View full text |Cite
|
Sign up to set email alerts
|

Early Application of Microsurgical Flaps in the Electric Burns of Extremities: A Two Institutional Case Series

Abstract: Some groups have avoided early microsurgical flaps in electrical burns under the pretext of injury to the microvasculature, which could increase vascular thrombosis. However, this option frequently results in amputation of the extremity. This study aims to evaluate the early application of microsurgical flaps for the treatment of electrical burns of extremities. A case series was retrospectively evaluated including patients with electrical trauma in extremities undergoing early microsurgical reconstruction. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…After applying inclusion and exclusion criteria, 31 articles were included in the qualitative and quantitative synthesis. 8–10,18–46 A flow chart of the study inclusion process and the reasons justifying the exclusion of the 166 studies are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After applying inclusion and exclusion criteria, 31 articles were included in the qualitative and quantitative synthesis. 8–10,18–46 A flow chart of the study inclusion process and the reasons justifying the exclusion of the 166 studies are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the well-selected patient, it allows one-stage reconstruction of complex defects with optimal functional and cosmetic results and low morbidity. Despite the reported higher rate of complications compared to other clinical scenarios, free flaps may reduce the number of surgical procedures required to achieve wound closure and, in selected cases, represent an opportunity for limb salvage [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Las quemaduras eléctricas ocasionan un extenso daño en los tejidos blandos al alterar la macro y microvasculatura local. Los primeros informes sobre el uso de colgajos microquirúrgicos en pacientes con quemaduras, según Castro et al 1 , datan de la segunda mitad de la década de 1970. Sin embargo, tal como lo evidenciaron Grotting et al 2 , el primer caso de colgajo libre utilizado para la cobertura de una quemadura eléctrica aguda fue descrito en 1982; en dicha ocasión, al paciente se le realizó un injerto con un colgajo libre de dorsal ancho más injerto de piel de espesor parcial.…”
Section: Introductionunclassified